Human Capital Strategies in the Face of Digitalization: A Review of the Literature to Improve Organizational Competitiveness - Putri, Raudia Maharani Saskia (Green Publisher Indonesia, 2025)
In the digital era, many organizations struggle to align their human capital strategies with rapid technological changes, resulting in suboptimal competitiveness and innovation. This study analyzes how human capital strategies can enhance organizational competitiveness by integrating digital competency development, innovation capacity, and strategic human resource management. A qualitative research design was employed using the Systematic Literature Review (SLR) method, reviewing 13 empirical studies from reputable databases such as Scopus, Sinta, and Google Scholar, published between 2015 and 2024. The findings reveal that investment in human capital through education, training, and learning is essential for sustaining organizational performance. Furthermore, digital transformation significantly drives innovation through improved human capabilities, motivation, and opportunities. Human resources are the foundation for competitive advantage, but challenges like digital skill gaps and adaptive readiness require strategic interventions. The study proposes an integrated framework of human capital strategies tailored to digitalization needs. These insights are expected to guide organizational leaders in developing effective human capital strategies to remain competitive in the digital economy. Future research is recommended to examine empirical evidence on the direct impact of human capital strategies across diverse industries.